Classification criteria and activity index of the debut of Lupus in pediatric patients hospitalized at the Instituto Nacional de Salud del Niño - Schult-Montoya, Sandra (2024)
Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease with a clinical debut in 15% to 20% of cases during childhood, most of them with a more severe course compared to SLE during adulthood. This study aims to determine the classification criteria and disease activity index at the time of onset in pediatric patients hospitalized between 2014 and 2019 at the Instituto Nacional de Salud del Niño, one of the most specialized pediatric institutes located in Lima, Peru. Only 39 medical records met the inclusion criteria. The mean age at onset was 12.3±2.7 years, with 87.2% of cases occurring in females. The average duration of the disease was 94.9 days (Min: 3 days - Max: 800 days). ANA (+) was present in all cases, followed by hypocomplementemia and renal involvement. The systemic lupus erythematosus disease activity index (SLEDAI) was used at the time of hospitalization, with a mean score of 19.1±7.7. The most frequent disease activity descriptors at admission were hypocomplementemia (87.2%), followed by Anti-dsDNA antibodies (+) (64.1%), hematuria, and fever (61.5%).